Exploring the marketing challenges faced by assembled computer dealers - Kallimani, Rashmi (2010)
There has been a great competition in computer market these days for obtaining higher market share. Computer market consisting of many branded and non branded players have been using various methods for matching the supply and demand in best possible way for attaining market dominance. Branded companies are seen to be investing large amount in aggressive marketing techniques for reaching the customers and obtaining higher market share. Due to this many small companies and non branded computer dealers such as assembled computer dealers (ACDs) etc are facing various challenges in marketing their products and services. Along with this even changing customer needs, life style, globalisation, consumption behaviour and technological advancement have added up for challenges. This study explores the challenges faced by the assembled computer dealers in selling and marketing of assembled desktops (ADTs). The study also explores the customer buying behaviour, perception and requirements for computer in order to find the gaps in what customers look for and the marketing practices followed by the ACDs. In depth face to face interviews were conducted for collecting the information on marketing practices followed by ACDs. Interviews were also conducted with customers to know their requirements and the process they go through while buying the computer. Based on the literature and the customer interview data, questionnaire was developed and administered among customers at a shopping mall in KL, which is known to be the hub for electronic equipments in KL especially for computers. The questionnaire was used for obtaining the general data on customer buying behaviour, their perception and their requirements while purchasing computer. A total of 100 respondents participated in this questionnaire based survey. The interview data and the survey data were analysed. The results indicated the gaps in marketing practices followed by ACDs in reaching and satisfying their customers. Based on the competitive position occupied by assembled computer market, the effect of external forces such as political, economical, social etc in external environment and the gaps existing in the marketing practices, tasks and strategies were suggested for ACDs for overcoming the marketing challenges and for further improvement in their business. This study is being conducted for one of the computer component manufacturing company (say ABC) located in Kuala Lumpur, who run a program to help ACDs in marketing of ADTs.